2011
DOI: 10.5350/dajpn2011240206t
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Psychiatric Symptoms in The Patients With Type 2 Diabetes Mellitus

Abstract: Quality of life and psychiatric symptoms in the patients with type 2 diabetes mellitusObjective: The purpose of this study is to measure the depression and anxiety levels, to investigate their associations with sociodemographic variables and to emphasize the importance of multidisciplinary approach for the follow up and treatment of patients with type 2 diabetes mellitus (DM). Method: We enrolled randomly selected 100 consecutive patients with type 2 DM, admitted to the outpatient clinic of endocrinology. Age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Accordingly, a number of studies have investigated the impact of physical, cognitive, and emotional changes on the treatment of diabetes and patient's quality of life. Quality of life is accepted as a significant indicator for the course of the disease in DM (3)(4)(5)(6). Good glycemic control (7), a reduction of severe metabolic complications (8), regular exercise (9), and improvement in compliance with behavioral models like education about the disease, healthy nutrition, and stress management (10) have been shown to increase the quality of life for persons with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a number of studies have investigated the impact of physical, cognitive, and emotional changes on the treatment of diabetes and patient's quality of life. Quality of life is accepted as a significant indicator for the course of the disease in DM (3)(4)(5)(6). Good glycemic control (7), a reduction of severe metabolic complications (8), regular exercise (9), and improvement in compliance with behavioral models like education about the disease, healthy nutrition, and stress management (10) have been shown to increase the quality of life for persons with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…1 – 5 Like all other chronic diseases, DM can lead to physical, mental, and social problems. 6 , 7 As blood glucose levels affect brain and mental functions, mental disorders particularly depression and anxiety disorders are more prevalent in patients with DM than in the general population. 8 – 13 Several studies on the issue have demonstrated that ~30% of the patients with DM exhibit depression symptoms and 20% exhibit anxiety symptoms and that DM increases the risk of mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Birçok çalışmada hipertansiyon, kardiyovasküler hastalıklar, obezite, insülin direnci, DM gibi kronik hastalıklarının uyku kalitesi ve düzenini düşürdüğü bildirilmiştir [3][4][5]. Tip 2 DM'de hipoglisemi ve hipergliseminin yanı sıra uyku bozuklukları da en sık karşılaşılan problemlerden biridir [6].…”
Section: Introductionunclassified